Supply Chain Performance Evaluation: Evaluating Rolls-Royce Supply Chain Performance in the Civil Aerospace Business Operations. - Agbi, Raymond.O. (2010)
Efficient supply chain performance has become a potentially valuable way of securing competitive advantage and improving organizational performance since competition is no longer between organizations, but among supply chains (Li et al, 2005). This study examines supply chain practices and performance in organization using Rolls-Royce Plc as a case study. The report also examines the contribution of supply chain management practices to organizational performance. A five-dimension framework of supply chain management practices/attributes was used to assess the performance of Rolls-Royce Supply Chain Units (SCUs) and the impact of the performance on its organizational goal. The 5-attributes of the framework are: (1) automation and integration, (2) resource and process quality, (3) product and service delivery, (4) Cost Containment, and (5) innovation and learning. The report specifically examined the supply chain practices and activities of Rolls-Royce’s 8 supply chain units (SCUs) using a questionnaire developed from the five dimension of the framework. The questionnaire was administered by interview and responded to by 10 managers in the SCUs and Supply Chain Planning and Control Unit (SCPC). The SCUs and SCPC are operational units responsible for planning, sourcing and delivery of material, components and parts for composite engine production. The results from the study shows an overall supply chain performance of 64 percent across the 5 dimensions. Since an integrated supply chain approach was adopted, this performance level was generalised to incorporates both suppliers’ and customers’ contribution in the overall rating. Resource and process quality attribute had the highest performance rating of 68 percent; this is consistent with the company’s known core competence – quality. Innovation and learning attribute had the least score of 56 percent. The key weaknesses identified or reasons for the overall performance rating include non-integration of some suppliers (especially sub-tier), inappropriate integration of some facilities in North America due to dissimilar software, suppliers capacity/capability challenge and demand management problem. Others reasons include; process non-compliance by internal and external suppliers, poor inter-SCU learning, knowledge-sharing and collaboration, high inventory holding cost and inadequate collaboration and resource-sharing with supplier, partners and customers. This shows that the biggest challenges of global supply chain management in organizations still lies within the critical success factor (CSF), and not the external factors of uncertainty, disasters, trade regulations, currency volatility etc. The report also shows that the five attributes are reinforcing within a loop. That is; lack of integration (by automation) affects efficient use of available resources and this affects quality output and delivery lead time. When this is the case, cost rise steeply through urgent purchases (to maintain buffers and mitigate production stoppage) and premium freighting and this takes a toll on inventory holding cost. Also when processes and procedures are inefficient, effort would be concentrated a managing risks and uncertainties escalation; and this negates proactive work-methods and procedures/approach which drives innovation, learning and continuous improvement. To overcome these challenges appropriate recommendations are proffered in chapter 6 to improve the level of integration, process compliance, delivery reliability, cost management within Rolls-Royce supply chain in order to guarantee better customer satisfaction and improve overall organizational performance.